DETERMINATION OF GAS-CONDENSATED FACTORS BASED ON COMPOSITION WITH NEWTON-RAPHSON ITERATION METHOD - Supahar Supahar (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2001)
The purpose of this research was to determine z-factor of gascondensate system using an iterative Newton-Raphson method to solve the Soave-Redlich-Kwong cubic equation of state (SRK CEOS). In this study, some influencingfactors were observed, i.e., compositions of hydrocarbon, temperature, and pressure of the gas condensate system. The research method involves determination process of the Hepthane plus characteristic. i.e. Critical Temperature of C7+ (T; C7+), critical pressure of C7+ (PcC7+). and acentricfactor of Cv; (COC7+) using Riazi and Duabert equation; and the flash liberation process to determine the compositions of hydrocarbon gas at certain pressure (P) and temperature (T). Comparison of the z-factors calculated using Newton-Raphson method to solve the SRK-CEOS with modified Dranchuk Abou-Kassem equation and Standing-Katz method yield an average different of 0.3419 percent and 1.13 percent.